Effect of Rhizobacteria Inoculation via Soil and Seeds on Glycine max L. Plants Grown on Soils with Different Cropping History - Denise Almeida Fonseca Fiuza; Luciana Cristina Vitorino; Edson Luiz Souchie; Moacir Ribeiro Neto; Layara Alexandre Bessa; Cintia Faria da Silva; Natasha Taline Trombela (Microorganisms, 2022)
Field experiments testing the effect of phosphate-solubilizing rhizobacteria (PSRB) should consider the cropping history and the method used to inoculate the strains. We evaluated the hypothesis that PSRB previously isolated from soybean seedlings could be effective in promoting growth in this oilseed crop in soils with different cultivation periods. We also evaluated whether this growth promotion could be influenced by cultivation histories or the inoculation method (via seeds or soil). Thus, we conducted an experiment in five fields cultivating Glycine max during two seasons (2019/2020 and 2020/2021), to test the effectiveness of PSRB (SAF9-Brevibacillus sp., SAF11-Brevibacillus sp., and SAC36-Bacillus velezensis) compared with results observed for the inoculant BiomaPhos (mix of Bacillus subtilis and Bacillus megaterium). The present study was based on the evaluation of vegetative growth, nutritional and yield parameters, and microbial biomass carbon (MBC). PSRB were more effective than, or showed similar effectiveness to, BiomaPhos for most of the evaluated vegetative, nutritional, and yield characteristics. In the fields tested in the summer 2019/2020 crop, SAC36 and SAF9 strains stood out as growth promoters, whereas in the 2020/2021 crop, SAF11, SAC36, and BiomaPhos were notable. There did not seem to be a direct relationship between long histories of soybean cultivation as a monoculture and low yield in the field. However, yield seems to be associated with soil nutritional characters such as Ca, Mg, K, P, cation exchange capacity, and organic matter levels. PSRB inoculation positively affected nodulation (NN) and nodule dry mass (NDM) in the evaluated fields in the 2019/2020 crop, and the aerial part dry mass (APDM), NN, NDM, yield, and MBC of the evaluated fields in the 2020/2021 crop. In contrast, the inoculation method was observed to have a strong effect on APDM, NN, root dry mass, and MBC, as the plants inoculated via seed showed higher mean values than those in the plants inoculated via soil. This study demonstrated the growth-promoting potential of new phosphate-solubilizing strains, which may eventually be incorporated by the biostimulants market to freely compete with BiomaPhos.